ENERGY ABSORPTION OF PRE-FOLDED TUBE WITH STIFFNESS GRADIENT - MEN Heng; CHEN WeiDong; TIAN XiaoGeng (Jixie qiangdu)
In order to solve the problems of high peak force and low energy absorption efficiency of traditional thin-walled square tubes during impact,the octagonal pre-folded tube was proposed by introducing creases on the surface of square tubes.The finite element software ABAQUS/Explicit was used to simulate the deformation mode and energy absorption under quasi-static compression. The results show that,compared with the square tube,the introduction of crease reduces the maximum peak force Pmax,increases the mean crushing force Pm,and forms the stiffness gradient crease tube,which produces a small crush force in the early stage of compression,which is beneficial to protect the main structure. With the increase of compression,the reaction force increases,and the energy absorption performance of the folded tube is improved Based on the study of the influence of the number of standard segments M,c/l,and b/t on the energy absorption performance of the pre-folded tube,the optimized structure of the pre-folded tube to improve the energy absorption performance of the pre-folded tube is obtained,which provides a reference for the application of the automobile energy absorption components.